Probability and statistical physics in St. Petersburg - St. Petersburg School in Probability and Statistical Physics (Saint Petersburg, Russia 18-29 June, 2012); Sidoravicius, V.; Smirnov, S. (Providence : American Mathematical Society, 2016)
This book brings a reader to the cutting edge of several important directions of the contemporary probability theory, which in many cases are strongly motivated by problems in statistical physics. The authors of these articles are leading experts in the field and the reader will get an exceptional panorama of the field from the point of view of scientists who played, and continue to play, a pivotal role in the development of the new methods and ideas, interlinking it with geometry, complex analysis, conformal field theory, etc., making modern probability one of the most vibrant areas in mathematics.
Includes bibliographical references and index.
Keywords: Probabilities -- Congresses; Statistical physics -- Congresses